Influence of the medication environment on the unsafe medication behaviour of nurses: A path analysis. Issue 15 (6th June 2018) - Yu, Xi; Li, Ce; Gao, Xueqin; Liu, Furong; Lin, Ping
Abstract : Aims and objectives: To explore the relationship between the medication environment and the unsafe medication behaviour of nurses and to analyse its influence path. Background: Unsafe medication behaviour is the direct cause of medication error. The organisational environment is the foundation of and plays a guiding role in work behaviour. Whether the medication environment correlates with the unsafe medication behaviour of nurses remains unclear. Design: This study used a correlative design with self‐administered questionnaires, and the SHEL model, an acronym of its elements of software, hardware, environment and liveware, was used as the framework for the medication environment. Methods: A survey was conducted among 1, 012 clinical nurses from five tertiary hospitals in China using the nurse unsafe medication behaviour scale and the nurses' perceptions of the medication environment scale. Data were collected from January–February 2017. Path analyses were used to examine the hypothesised model. Results: The medication environment correlated negatively with unsafe medication behaviour ( r  = −.48, p  < .001). The path analysis showed that software, liveware and nurses' personal factors directly affected unsafe medication behaviour. Software, hardware and the environment indirectly influenced unsafe medication behaviour, and nurses' personal factors played a mediating role in the relationships of unsafe medication behaviour with software, hardware and the environment. Conclusion: The unsafe medication behaviour of nurses should be further improved. The medication environment was a predictor of unsafe medication behaviour. Care managers should actively improve the medication environment to reduce the incidence of unsafe medication behaviours. Relevance to clinical practice: Effective strategies for nursing are needed, particularly those that optimise the rules and regulations process and that target the development of staff training programmes. Additionally, a nonpunitive safety culture should be established, and information management and team cooperation should be strengthened.